Validity Analysis of the OrDeP2E Model of Physics Learning Tools to Improve Critical Thinking Skills of High School Students - Hamsa Doa; Yasinta Embu Ika (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study was to determine the feasibility of the physics learning model of the OrDeP2E model to improve the critical thinking skills of high school students. The learning tool developed was assessed by two validation experts who were folus in the process of construct validity testing and the contents of the developed device. Validation data were obtained assesment sheet using categories 1-4. This study refers to the development of the 4-D model. Validated tools are 1) Syllabus, 2) lesson plan 3) student textbooks, 4) student worksheet, and 5) Critical thinking skills test. The results showed that 1) the syllabus got a score of 3.58 (valid), 2) the RPP got a score of 3.83 (very valid), 3) the BAS got a score of 3.54 (valid), 4) the worksheet received a score of 3.78 ( very valid), critical thinking skills test get a score of 3.70 (very valid). Based on the research results, learning tools are appropriate to be used to improve critical thinking skills of high school students.